SINTREN’S SACRED CADENCE: Journeying into the Mystical Dimensions of Spiritual Rhythms - Busro, Busro (Ulul Albab: Jurnal Studi Islam, 2023)
This article investigates the mystical dimension embedded within the traditional Javanese performance art of Sintren, revealing its function as a medium for spiritual experience and transcendence. Employing a qualitative research approach, the study draws on Annemarie Schimmel’s theoretical framework on Islamic mysticism and incorporates in-depth analysis of Sintren performances, alongside field research involving practitioners, artists, and audience members. The research seeks to understand how Sintren facilitates spiritual engagement and mystical encounters within a cultural and performative context. Findings demonstrate that Sintren operates not merely as a ritual or cultural performance, but as a tangible expression of mysticism deeply rooted in Javanese spiritual consciousness. Through the interplay of music, dance, trance states, and symbolic language, Sintren creates a sacred space in which participants and observers alike experience a connection with the Divine. This mystical interaction transcends performative boundaries, offering both performers and audiences moments of transcendence and inner transformation. The study underscores how traditional art forms serve as vital vehicles for spiritual expression, embedding metaphysical themes within cultural practices. By highlighting the convergence of art and spirituality, this research contributes to broader discourses in religious studies, anthropology, and performance theory. It also underscores the urgent need to preserve and critically study cultural expressions like Sintren, which encapsulate rich, localized interpretations of the sacred. Ultimately, this research affirms that traditional art forms are not only aesthetic phenomena but also powerful conveyors of mystical experience and spiritual identity within indigenous cultural frameworks.